2013
DOI: 10.1111/j.1539-6975.2013.12007.x
|View full text |Cite
|
Sign up to set email alerts
|

Why (Re)insurance is Not Systemic

Abstract: The traditional model of (re)insurance lacks the elements that make a financial institution systemically important: risks are effectively pulverized; liabilities tend to be prefunded, which eliminates most of the leverage in the traditional sense; and active asset‐liability management reduces most of the liquidity mismatch that traditionally propagates systemic risk. (Re)insurers that have stuck to this traditional business model have successfully weathered the crisis, even playing a stabilizing role. Unfortun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 6 publications
1
26
1
Order By: Relevance
“…Whether the insurance sector poses a systemic risk is a fundamental issue, and varying opinions have emerged. Kessler () adheres to the traditional view that insurers are not systemically risky. The argument is premised largely on the observation that the traditional insurance balance sheet lacks those characteristics typically associated with systemic risk in other financial institutions.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Whether the insurance sector poses a systemic risk is a fundamental issue, and varying opinions have emerged. Kessler () adheres to the traditional view that insurers are not systemically risky. The argument is premised largely on the observation that the traditional insurance balance sheet lacks those characteristics typically associated with systemic risk in other financial institutions.…”
Section: Related Literaturementioning
confidence: 99%
“…Although policy measures for systemically important insurers are now being phased in, much controversy still exists about whether the insurance sector poses a systemic risk and, if so, how this risk should be measured and how systemically important insurers should be regulated. Industry representatives have argued that overall, insurers enhance financial stability rather than pose a systemic risk (Kessler, ). Previous research has criticized the regulatory assessment methodology (Weiß and Mühlnickel, ; Bierth, Irresberger, and Weiß, ), and researchers have argued that a systemic risk regulator for insurance companies would erode market discipline (Harrington, ).…”
Section: Introductionmentioning
confidence: 99%
“…The windup of an insurer is an orderly process and does not lead to an immediate default on liabilities, the fire sale of assets, or increased cash outflow. Indeed, this process can take up to several years, as described by Kessler (). In principle, this view is shared by the IAIS (), which assesses global systemically important insurers and places only minor weight on traditional life and nonlife underwriting activities…”
Section: Systemic Risk In the Insurance Sectormentioning
confidence: 99%
“…The latter reference analyzes the ability of the insurance industry to disrupt the financial market. It is indeed observed that insurers may contribute to the instability of the financial sector, especially through their noncore activities, see [7][8][9][10][11]. These observations are based on systemic risk measures that allow for the study of the interconnectedness between insurers and other financial institutions, see [12][13][14].…”
Section: Introductionmentioning
confidence: 99%